A remark on the intersection of the conjugates of the base of quasi-HNN groups - R. M. S. Mahmood (International Journal of Mathematics and Mathematical Sciences)
Quasi-HNN groups can be characterized as a generalization of HNN groups. In this paper, we show that if G∗ is a quasi-HNN group of base G, then either any two conjugates of G are identical or their intersection is contained in a conjugate of an associated subgroup of G.